A pandemia do Covid-19 e o impacto sobre o emprego formal feminino no Brasil - Arruda, Flávia Nicácio de (Brasil, 2024)
Economic crises often reveal and exacerbate pre-existing inequalities, and the COVID-19 pandemic was no different. Women, historically subjected to disparities in the labor market, were significantly affected. The aim was to analyze the impact of the COVID-19 pandemic on formal female employment in Brazil. The research adopted a qualitative-quantitative approach, utilizing data from the Continuous National Household Sample Survey (PNAD) by the Brazilian Institute of Geography and Statistics (IBGE) and information from the Annual Social Information Report (RAIS) from 2016 to 2021. The PNAD provided both qualitative and quantitative data on the labor market, while the RAIS offered detailed information on formal jobs by economic sectors. The data covered hirings, dismissals, education level, working hours, salaries, and types of occupation, among other aspects. This approach allowed for a comprehensive analysis of the impact of the COVID-19 pandemic on formal female employment in Brazil. The study e